Testing a mobile app for child abuse treatment: A mixed methods study - Shuhong Luo; Ann S. Botash (Elsevier, 2020)
Objective: This study provides a preliminary evaluation of the usability and acceptability of a mobile application (sexual assault care algorithm, SACA). Methods: An explanatory sequential mixed methods research was used. A quantitative survey was followed up by a qualitative study. A convenience sample of participants (n = 4) was recruited. The research was conducted on a one-on-one basis. In the quantitative phase, a random assignment technique was used to divide four participants into two groups of two participants each. Post-Study System Usability Questionnaire(PSSUQ) and Acceptability e-Scale were used to collect quantitative data. In the qualitative phase, interview, observation, and documentation were used to collect qualitative data. Data were analyzed both quantitative and qualitatively. The qualitative data were linked with the initial quantitative data to determine how the follow-up qualitative data helped explain the initial quantitative results. Results: The quantitative results suggested that SACA has high usability (5.05 ± 1.83) and acceptability (3.81 ± 1.22). The qualitative results further indicate that the participants thought SACA was easy to use and useful, and most of them would recommend it to others. Areas of improvement include adding features that would calculate and validate the elapsed time since the sexual assault, adding explanations to some buttons, and providing training. Conclusions: Our findings highlight the value of using a mixed methods research design to conduct a usability and acceptability test. Nurses are more likely to adopt a new technology for their evidence-based practice when the technology is easy to use and useful and requires less time to find the right piece of guideline evidence. Individualized training needs to be designed based on users' characteristics.